An invasive adenocarcinoma of the accessory parotid gland: a rare example developing from a low-grade cribriform cystadenocarcinoma? - Nakatsuka Shin-ichi; Harada Hiroshi; Fujiyama Hiroshi; Takeda Koji; Kitamura Koji; Kimura Hayato; Nagano Teruaki; Ito Mahito; Asada Yuji (BMC, 2011)
Abstract Low-grade cribriform cystadenocarcinoma (LGCCA) is a rare tumor of the salivary gland that exhibits clinically indolent behavior. In this paper, we present a case of invasive adenocarcinoma of the accessory parotid gland in a young male that exhibited histology suggestive of an association of LGCCA. A 27-year-old man presented with a subcutaneous tumor in his left cheek. The tumor was separated from the parotid gland and located on the masseter muscle. The tumor was resected, and the postoperative histological diagnosis was adenocarcinoma, not otherwise specified (ANOS). The tumor exhibited papillary-cystic and cribriform proliferation of the duct epithelium and obvious stromal infiltration. Some tumor nests were rimmed by myoepithelium positive for smooth muscle actin, p63, and cytokeratin 14, indicating the presence of intraductal components of the tumor. Tumor cells exhibited mild nuclear atypia, and some of them presented an apocrine-like appearance and had cytoplasmic PAS-positive/diastase-resistant granules and hemosiderin. Other cells had foamy cytoplasm with microvacuoles. Immunohistochemistry revealed that the almost all of the tumor cells were strongly positive for S-100. These histological findings suggest the possibility that ANOS might arise secondarily from LGCCA. This is an interesting case regarding the association between ANOS and LGCCA in oncogenesis. Virtual Slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1226764594634693.